Pengaruh Suhu Pemadatan Campuran Untuk Perkerasan Lapis Antara (AC-BC) - Raharjo, Budi; Pratomo, Priyo; Ali, Hadi (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2016)
The main objective of this study was to determine the influence of variations of temperaturechanges on the asphalt compaction process heat (hot mix asphalt) layer between (AC - BC)against Marshall parameter with reference to the specifications of Highways in 2010.Based on the analysis of data processing obtained that the value content of asphalt used formiddle limit is 6.1 % and the lower limit of 6.85 %.Based on the analysis of data processing obtained that the value content of asphalt used formiddle limit is 6.1 % and the lower limit of 6.85 %. From the test results Marshall at atemperature of 135oC, 145oC and 155oC in the middle limit has met all the parameters Marshall.Only at a temperature of 125oC and 115oC that do not meet the parameters Marshall Void in valuedue Mix (VIM) and the Marshall Quotient (MQ) do not enter Specifications Highways Marshall2010. While testing the lower limit on the temperature 115oC, 125oC and 135oC does not meet allthe parameters Marshall, because the value of Marshall Quotient (MQ) did not enter thespecifications of Highways in 2010 .Keywords : Solidification temperature , Specification for Highways 2010, Marshall , AsphaltConcrete - Binder Course (AC - BC)